A highly potent and safe pyrrolopyridine-based allosteric HIV-1 integrase inhibitor targeting host LEDGF/p75-integrase interaction site - Maehigashi, Tatsuya; Ahn, Seohyun; Kim, Uk-Il; Lindenberger, Jared; Oo, Adrian; Koneru, Pratibha C.; Mahboubi, Bijan; Engelman, Alan N.; Kvaratskhelia, Mamuka; Kim, Kyungjin; Kim, Baek (PLoS pathogens, 2021)
Allosteric integrase inhibitors (ALLINIs) are a class of experimental anti-HIV agents that target the noncatalytic sites of the viral integrase (IN) and interfere with the IN-viral RNA interaction during viral maturation. Here, we report a highly potent and safe pyrrolopyridine-based ALLINI, STP0404, displaying picomolar IC 50 in human PBMCs with a >24,000 therapeutic index against HIV-1. X-ray structural and biochemical analyses revealed that STP0404 binds to the host LEDGF/p75 protein binding pocket of the IN dimer, which induces aberrant IN oligomerization and blocks the IN-RNA interaction. Consequently, STP0404 inhibits proper localization of HIV-1 RNA genomes in viral particles during viral maturation. Y99H and A128T mutations at the LEDGF/p75 binding pocket render resistance to STP0404. Extensive in vivo pharmacological and toxicity investigations demonstrate that STP0404 harbors outstanding therapeutic and safety properties. Overall, STP0404 is a potent and first-in-class ALLINI that targets LEDGF/p75 binding site and has advanced to a human trial.